A DILEMMA IN TEACHING ELEMENTARY ACCOUNTING. - Fryxell, C. A. (The Accounting Review, 1935)
Abstract In accordance with the request that this session be a discussion of practical problems of teaching elementary accounting, the author of this paper tries to be as practical as possible. Far from hoping to present anything entirely new, either as to problems or solutions, he treats of a situation which merits consideration chiefly because it is old, and consequently of common occurrence. It is a problem with which most instructors are only too well acquainted. The instructor of beginning accounting at most small colleges faces a dilemma. This dilemma is the necessity, and at the same time the difficulty, of teaching in one class two widely different types of students, those who are taking only the one course as part of their general education; and those who intend it as a groundwork for further study toward a major in accounting. The student, who is planning to continue with accounting as his field of work, needs above all else a solid foundation for the more advanced courses. Possibly if a group of accounting instructors were to name just two results as the most valuable to be desired from the beginning course, they would specify first, thoroughness, and second, accuracy.